2022
DOI: 10.2196/38942
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Digital Care Programs for Musculoskeletal Conditions on Depression and Work Productivity: Longitudinal Cohort Study

Abstract: Background Comorbidity between musculoskeletal (MSK) pain and depression is highly common, and is associated with a greater symptom burden and greater loss of work productivity than either condition alone. Multimodal care programs tackling both physical and mental health components may maximize productivity recovery and return to work. Digital delivery of such programs can facilitate access, ensure continuity of care, and enhance patient engagement. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 128 publications
1
4
0
Order By: Relevance
“…Although the magnitude of the reduction in absenteeism was not statistically significant, there were significant improvements in presenteeism, work productivity impairment, and overall activity impairment in both unadjusted and adjusted analyses of approximately 20% each. This findings in our study targeting those seeking help with mood and anxiety management is consistent with the magnitude of the effect seen in other studies examining work productivity improvements among interventions targeting comorbid conditions such as pain (~20% reduction in work productivity impairment), 22 insomnia (~14% reduction in activity impairment), 23 and musculoskeletal disorders (~20% in work productivity impairment) 24 . This is not surprising given the strong correlation between depressive symptoms, anxiety symptoms, and work productivity found in prior studies 1–5 (2004) as well as our own (eg, the correlations ranged from 0.52 to 0.63 in the present study).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the magnitude of the reduction in absenteeism was not statistically significant, there were significant improvements in presenteeism, work productivity impairment, and overall activity impairment in both unadjusted and adjusted analyses of approximately 20% each. This findings in our study targeting those seeking help with mood and anxiety management is consistent with the magnitude of the effect seen in other studies examining work productivity improvements among interventions targeting comorbid conditions such as pain (~20% reduction in work productivity impairment), 22 insomnia (~14% reduction in activity impairment), 23 and musculoskeletal disorders (~20% in work productivity impairment) 24 . This is not surprising given the strong correlation between depressive symptoms, anxiety symptoms, and work productivity found in prior studies 1–5 (2004) as well as our own (eg, the correlations ranged from 0.52 to 0.63 in the present study).…”
Section: Discussionsupporting
confidence: 91%
“…28 Respondents are asked about various symptoms over the past 2 weeks and to indicate whether symptoms occurred not at all (0), on several days (1), more than half the days (2), or nearly every day (3). Summed scores range from 0 to 24, categorized according to severity level as minimal/less than mild (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24).…”
Section: Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of depression and anxiety has been reported to be higher in residents of rural areas compared to urban areas [ 76 ], with those from rural areas facing a shortage of mental health services [ 77 ]. Since mental health and MSK pain are tightly associated [ 38 , 78 ], the scarcity of psychological support can seriously impact the recovery rates of rural populations. This study confirms a higher depression burden in patients from rural areas but found similar improvement in mental health scores in both rural and urban patients, reinforcing the notion that lack of access to mental health resources may be the main driver for the higher burden of disease in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…This program encourages patients to develop strategies and self-management skills to manage their pain and has been validated in several acute and chronic MSK conditions [15][16][17][34][35][36]. Additionally, the impact of race and ethnicity [37], as well as baseline mental health [38] and fear-avoidance beliefs [39], on final clinical outcomes have also been explored. The purpose of this study was to assess the impact of geographical location on engagement and clinical outcomes after a multimodal DCP, with the hypothesis being that patients from both rural and urban areas would have similar engagement and significant improvement in outcomes after program completion.…”
Section: Introductionmentioning
confidence: 99%